Release Kinetics Modelling and in Vivo-Vitro, Shelf-Life Study of Resveratrol Added Composite Transdermal Scaffolds - Çiftçi, Fatih (Elsevier, 2023)
In this article, the suitability of composite transdermal biomaterial for wound dressing applications is discussed. Bioactive, antioxidant Fucoidan and Chitosan biomaterials were doped into polyvinyl alcohol/β-tricalcium phosphate based polymeric hydrogels loaded with Resveratrol, which has theranostic properties, and biomembrane design with suitable cell regeneration properties was aimed. In accordance with this purpose, tissue profile analysis (TPA) was performed for the bioadhesion properties of composite polymeric biomembranes. Fourier Transform Infrared Spectrometry (FT-IR), Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM-EDS) analyses were performed for morphological and structural analyses of biomembrane structures. In vitro Franz diffusion mathematical modelling of composite membrane structures, biocompatibility (MTT test) and in vivo rat tests were performed. TPA analysis of resveratrol loaded biomembrane scaffold design; compressibility; 13.4 ± 1.9(g.s), hardness; 16.8 ± 1(g), adhesiveness; − 11 ± 2.0(g.s), elasticity; 0.61 ± 0.07, cohesiveness; 0.84 ± 0.04 were found. Proliferation of the membrane scaffold was 189.83 % at 24 h and 209.12 % at 72 h. In the in vivo rat test; at the end of 28th day, it was found that biomembrane_3 provided 98.75 ± 0.12 % wound shrinkage. The shelf-life of RES in the transdermal membrane scaffold, which was determined as Zero order according to Fick's law in in vitro Franz diffusion mathematical modelling, was found to be approximately 35 days by Minitab statistical analysis. The importance of this study is that the innovative and novel transdermal biomaterial supports tissue cell regeneration and cell proliferation in theranostic applications as a wound dressing.
Keywords: Chitosan; Biomembrane; Composite; Fucoidan; Resveratrol; Franz Diffusion